Effects of treatment processes on AOC removal and changes of bacterial diversity in a water treatment plant. (1st June 2022) - Chen, W.T.; Chien, C.C.; Ho, W.S.; Ou, J.H.; Chen, S.C.; Kao, C.M.
Abstract: The effectiveness of different treatment processes on assimilable organic carbon (AOC) removal and bacterial diversity variations was evaluated in a water treatment plant. The van der Kooij technique was applied for AOC analysis and responses of bacterial communities were characterized by the metagenomics assay. Results show that the AOC concentrations were about 93, 148, 43, 51, 37, and 38 μg acetate-C/L in effluents of raw water basin, preozonation, rapid sand filtration (RSF), ozonation, biofiltration [biological activated carbon (BAC) filtration], and chlorination (clear water), respectively. Increased AOC concentrations were observed after preozonation, ozonation, and chlorination units due to the production of biodegradable organic matters after the oxidation processes. Results indicate that the oxidation processes were the main causes of AOC formation, which resulted in significant increases in AOC concentrations (18–59% increment). The AOC removal efficiencies were 47, 28, and 60% in the RSF, biofiltration, and the whole system, respectively. RSF and biofiltration were responsible for the AOC treatment and both processes played key roles in AOC removal. Thus, both RSF and biofiltration processes would contribute to AOC treatment after oxidation. Sediments from the raw water basin and filter samples from RSF and BAC units were collected and analyzed for bacterial communities. Results from scanning electron microscope analysis indicate that bacterial colonization was observed in filter materials. This indicates that the surfaces of the filter materials were beneficial to bacterial growth and AOC removal via the adsorption and biodegradation mechanisms. Next generation sequencing analyses demonstrate that water treatment processes resulted in the changes of bacterial diversity and community profiles in filters of RSF and BAC. According to the findings of bacterial composition and interactions, the dominant bacterial phyla were Proteobacteria (41% in RSF and 56% in BAC) followed by Planctomycetes and Acidobacteria in RSF and BAC systems, which might affect the AOC biodegradation efficiency. Results would be useful in developing AOC treatment and management processes in water treatment plants. Graphical abstract: Image 1 Highlights: Ozonation and chlorination cause increase in AOC concentrations in water plant. Rapid sand filtration (RSF) and biofiltration can cause significant AOC removal. RSF and biofiltration units cause changes of bacterial diversity and community. Filtration and biodegradation mechanisms cause AOC removal in RSF/biofiltration. Proteobacteria, Planctomycetes, and Acidobacteria may cause AOC biodegradation.